A prática da coordenação pedagógica dos centros de educação de jovens e adultos de Primavera do Leste e de Rondonópolis - David, Gleibiane Silva (2016)
This survey is linked to the Graduate Program in Education, (PPGEDU/CUR/UFMT) in Teacher Training and Educational row and Public Policy. The object of study is the practice of pedagogical coordination in the Educational Center for Young and Adults of Primavera do Leste/MT and Rondonópolis/MT. The importance of this research is the contribution to the studies about pedagogical coordinator your practices, in specially how the professional can mediation the process of training with the coordinator of areas in the Educational Center for Young and Adults (CEJAs). Thus, the research question is: How the pedagogical coordinator can mediate the process of teacher training with the area coordinator in the Educational Center for Young and Adults of Primavera do Leste/MT and Rondonópolis/MT? The general objective of the research is to analyze the conceptions and formative practices of the pedagogic coordination that contribute to the mediation of the formation process with the coordinators of areas in the spaces of CEJAs of Primavera do Leste/MT and of Rondonópolis/ MT. Starting from the unfolding of the general objective the following specific objectives are had: understand how the coordination of Educational Center for Young and Adults can mediate the process of training with the areas coordinator; to understand how the formation process happens in the spaces of the Educational Center for Young and Adults and which the paper of the pedagogic coordination in that movement; to identify and to contemplate about the conceptions of pedagogic coordination, about the need of the / to coordinator / to know Pedagogy to develop his/her work. The research is structured in the qualitative approach, anchored in the perspective dialectics. The instruments to collect data selected are: observation, semi-structured interviews and documents analysys. The research takes as theorical and methodological the following authors: Freire (1983, 1991, 200a/b, 2001, 2005, 2015), Carvalho (2005, 2006, 2008, 2014, 2015a/b/c), Gadotti (1995), Paro (2010, 2015), Domingues (2014), Lüdke e André (1986), among others. I interviews four pedagogical coordinator. For more information interviewed six areas coordinators. The results of the research showed the form of mediation of training, performed by pedagogical coordination with area coordination, suffer influences from internals and externals determinations. The mediation done by the pedagogical coordinator is not a simples work, because the professional makes the training with the school group and after this, makes their interventions for the work happens to area of knowledge. The management meeting is an essential space to the coordinator mediate the training and talk to the area coordination. Yet, there have to be other moments for the coordinator make their interventions. Thus, there is no specific time for mediation, so it’s performed when there is a need or area coordinator seeks help of teaching. On the other hand, information collected indicate a challenge for the coordination of CEJA that is to provide a space and individualized time for the coordinators to hold discussions with each area coordinator, this moment of listening, dialogue, recognizing the needs of teachers and the areas of coordination is essential to the organization of the pedagogical work in CEJA.